2018 IEEE Conference on Decision and Control (CDC) 2018
DOI: 10.1109/cdc.2018.8619189
|View full text |Cite
|
Sign up to set email alerts
|

Rebalancing Frequency Considerations for Kelly-Optimal Stock Portfolios in a Control-Theoretic Framework

Abstract: In this paper, motivated by the celebrated work of Kelly, we consider the problem of portfolio weight selection to maximize expected logarithmic growth. Going beyond existing literature, our focal point here is the rebalancing frequency which we include as an additional parameter in our analysis. The problem is first set in a control-theoretic framework, and then, the main question we address is as follows: In the absence of transaction costs, does high-frequency trading always lead to the best performance? Re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…The reader is also referred to [9] for a rather comprehensive exposition covering many aspects of the theory. This paper is most closely related to more recent work such as [10]- [13] which provide results on the effect of rebalancing frequency on optimal trading performance. Specifically, in [12] and [13], it is shown that in a so-called idealized market with a stock satisfying a certain "sufficient attractiveness" condition, the buy and holder can match the performance of the high-frequency trader.…”
Section: Introductionmentioning
confidence: 90%
“…The reader is also referred to [9] for a rather comprehensive exposition covering many aspects of the theory. This paper is most closely related to more recent work such as [10]- [13] which provide results on the effect of rebalancing frequency on optimal trading performance. Specifically, in [12] and [13], it is shown that in a so-called idealized market with a stock satisfying a certain "sufficient attractiveness" condition, the buy and holder can match the performance of the high-frequency trader.…”
Section: Introductionmentioning
confidence: 90%
“…Consistent with the existing work in [11,13], for any rebalancing period n ≥ 1, we study the problem of maximizing the expected logarithmic growth…”
Section: Frequency-dependent Optimization Problemmentioning
confidence: 99%
“…which is classical in finance; e.g., see [4,5,13,17]. That is, with K ∈ K, we have a guarantee that 100% of the account is invested.…”
Section: Admissible Set Of Portfolio Weightsmentioning
confidence: 99%
See 2 more Smart Citations